2014
DOI: 10.4085/1062-6050-49.3.09
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Comparison of Injured High School Basketball Athletes Reporting to Emergency Departments and the Athletic Training Setting

Abstract: Patterns of injury differed among high school basketball players presenting for treatment in the emergency department and the athletic training setting. Understanding differences specific to clinical settings is crucial to grasping the full epidemiologic and clinical picture of sport-related injuries. Certified athletic trainers play an important role in identifying, assessing, and treating athletes with sport-related injuries who might otherwise present to clinical settings with higher costs, such as the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Strains and sprains are common injuries in athletes across competition levels 9,13,22,23,31,32 ; however, they are not typically considered conditions necessitating emergency transport. In our study, strains were the leading diagnosis among ETIs in collegiate sports and the third leading diagnosis among ETIs in high school sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains and sprains are common injuries in athletes across competition levels 9,13,22,23,31,32 ; however, they are not typically considered conditions necessitating emergency transport. In our study, strains were the leading diagnosis among ETIs in collegiate sports and the third leading diagnosis among ETIs in high school sports.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that having an AT present contributed to the overall low ETI rates in this study; however, our study did not directly examine the effect of AT coverage on the rate, proportion, or distribution of injuries requiring ETI. Previous studies 31,43,44 have shown ATs were able to manage and treat patients with less severe injuries without referral to the ED, and the presence of an AT has been associated with improved medical care of student-athletes. We did not consider other factors the AT must consider in his or her decision-making process (eg, the emotional stability of the athlete or the availability of alternative transportation), which may have resulted in an ETI for a nonemergent condition.…”
Section: Limitationsmentioning
confidence: 99%
“…3 When secondary schools lack athletic training services, they may have to rely on coaches or administrators or immediate referral to emergency services when an injury occurs. 4 The former may not have the proper medical education to appropriately treat musculoskeletal injuries, and use of the latter considerably increases the health care cost and burden to patients, parents, and the community. 5 More than 7.8 million high school students participate in organized sports in the United States each year.…”
mentioning
confidence: 99%
“…Such staff may help to reduce the burden of care provided in other settings such as hospitals, emergency departments, and specialty clinics. 12 Additionally, there is a large productivity gain for the parents of injured student-athletes, who would have to take time to transport their children to other service providers if ATs were not present in the schools.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because many high school student-athletes do not have access to a full-time AT, 9 they may seek therapy offsite. 12 This contrasts with collegiate student-athletes, who have access to a full-time AT and may receive onsite care.…”
Section: Comparison With College-level Treatment Datamentioning
confidence: 99%